2013
DOI: 10.1002/aqc.2324
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 17/0 circle hooks and bait on sea turtles bycatch in a Southern Atlantic swordfish longline fishery

Abstract: 1. The incidental catch of marine turtles is a major problem in commercial pelagic longline fisheries. The present paper reports marine turtle bycatch composition and rates from a Portuguese commercial longline fishery targeting swordfish in the South Atlantic, and investigates the effects of changes in hook style and bait type.2. In total, 310 longline sets were carried out between 2008 and 2012. Three different hook styles were tested, traditional J hook (9/0) and two 17/0 circle hooks (a non-offset and a 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…Santos et al . () concluded that significant reduction of bycatch of sea turtles, particularly for loggerheads ( Caretta caretta ) can be achieved in the Southern Atlantic by changing from J‐hooks to circle hooks, especially if baited with mackerel. As the voluntary adoption of circle hooks is more likely to happen if catch rates of target species are unaffected or increased, the effects of hook styles and bait types on the retained catch were addressed in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Santos et al . () concluded that significant reduction of bycatch of sea turtles, particularly for loggerheads ( Caretta caretta ) can be achieved in the Southern Atlantic by changing from J‐hooks to circle hooks, especially if baited with mackerel. As the voluntary adoption of circle hooks is more likely to happen if catch rates of target species are unaffected or increased, the effects of hook styles and bait types on the retained catch were addressed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The main object of the SELECT-PAL project was to assess the effects of different hook styles and bait type combinations on the catch rates and mortality of sea turtles, as these are an important vulnerable megafauna bycatch component of the Portuguese pelagic longline fishery operating in the Atlantic Ocean. Santos et al (2013) concluded that significant reduction of bycatch of sea turtles, particularly for loggerheads (Caretta caretta) can be achieved in the Southern Atlantic by changing from J-hooks to circle hooks, especially if baited with mackerel. As the voluntary adoption of circle hooks is more likely to happen if catch rates of target species are unaffected or increased, the effects of hook styles and bait types on the retained catch were addressed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, due to their predominant hooking location, organisms captured on circle hooks that will be handled and released require less handling time, minimizing stress (Cooke and Suski 2004). However, circle hooks are harder to remove and may result in more damage when removed relative to J-shaped hooks that are lodged in the same anatomical location (Santos et al 2013). …”
Section: Hook Shapementioning
confidence: 99%
“…Three were on catch rates (two on leatherbacks, one olive ridleys, Mejuto et al 2008;Coelho et al 2015), five on the proportion deeply hooked (three on loggerheads, two on leatherbacks, Watson et al 2005;Epperly et al 2012;Santos et al 2013;Coelho et al 2015), and four on at-vessel mortality rates (three on leatherbacks, one on loggerheads, Gilman et al 2007;Santos et al 2013;Coelho et al 2015). Most of these findings on bait type effect were from studies with simultaneous variability in hook shape and/or hook minimum width.…”
mentioning
confidence: 99%
“…Although the use of circle-hooks have been a promising method to reduce sea turtle by-catch in some long line fisheries (Santos et al 2013; Watson et al 2005; Sales et al 2010; Gilman et al 2007). there is variability in its effectiveness in Atlantic fleets (Huang et al 2016; Foster et al 2012; Fernandez-Garvalho et al 2015; Richards et al 2012).…”
Section: Potential Sea Turtle By-catch Mitigation Measures For Long Lmentioning
confidence: 99%